Microalgae-enabled wastewater remediation and nutrient recovery through membrane photobioreactors : Recent achievements and future perspective - Goh, Pei Sean; Noor Azlinda, Ahmad; Lim, Junwei; Liang, Yong Yeow; Kang, Hooi Siang; Ahmad Fauzi, Ismail; Arthanareeswaran, Gangasalam (MDPI, 2022)
The use of microalgae for wastewater remediation and nutrient recovery answers the call for a circular bioeconomy, which involves waste resource utilization and ecosystem protection. The integration of microalgae cultivation and wastewater treatment has been proposed as a promising strategy to tackle the issues of water and energy source depletions. Specifically, microalgae-enabled wastewater treatment offers an opportunity to simultaneously implement wastewater remediation and valuable biomass production. As a versatile technology, membrane-based processes have been increasingly explored for the integration of microalgae-based wastewater remediation. This review provides a literature survey and discussion of recent progressions and achievements made in the development of membrane photobioreactors (MPBRs) for wastewater treatment and nutrient recovery. The opportunities of using microalgae-based wastewater treatment as an interesting option to manage effluents that contain high levels of nutrients are explored. The innovations made in the design of membrane photobioreactors and their performances are evaluated. The achievements pave a way for the effective and practical implementation of membrane technology in large-scale microalgae-enabled wastewater remediation and nutrient recovery processes.